The Effect of Service Quality Toward Patient Loyalty in Special Hospital of South Sulawesi - Nurfitriani, Nurfitriani (Journal of Engineering Science and Technology Management, 2024)
The obligation of hospitals to continuously improve and ensure service quality is regulated in Article 40 of Law No. 44 of 2009 concerning hospitals. High-quality services create emotional bonds with patients, resulting in positive experiences and increased loyalty. Therefore, service quality is essential to achieving patient satisfaction, which fosters loyalty. This study aims to determine the influence of service quality on patient loyalty at the Special Hospital of South Sulawesi Province. This quantitative research used a cross-sectional design. The sample consisted of 147 returning patients who received services at the outpatient installation of Dadi Regional Special Hospital (RSKD). The results showed that service quality significantly affects patient satisfaction. Furthermore, service quality has a significant impact on patient loyalty. These findings highlight the importance for hospitals to remain committed to improving service quality as a strategic effort to increase patient satisfaction and loyalty. Enhancing satisfaction will, in turn, support hospital strategies and the achievement of organizational goals.